Factors Affecting the Reporting of Adverse Events Due to Medical Devices Among Doctors: A Qualitative Approach - Sandra, Anil; Kumar D, Mahesh; Palatty, Princy Louis; Febina MB (National Journal of Community Medicine, 2026)
Background: A medical device is any tool or gadget used to diagnose or treat a condition. These devices may be associated with Adverse Medical Device Events (AMDEs), ranging from minor complications to serious morbidity or mortality. Underreporting of AMDEs remains a significant challenge to patient safety and regulatory surveillance. The primary objective of this study was to explore doctors’ beliefs and behaviors related to the reporting of Adverse Medical Device Events (AMDEs). Secondary objectives were to identify other individual and organizational factors influencing the reporting of AMDEs. Methodology: A descriptive qualitative study was conducted using stratified purposive sampling to recruit doctors from a tertiary care hospital. Thematic saturation was attained by semi-structured interviews that lasted ten to fifteen minutes. Interviews were audio-recorded, transcribed verbatim, and analyzed using inductive thematic analysis with QDA Miner Lite. Methodological rigor was ensured through data saturation, reflexive analysis, and adherence to COREQ reporting guidelines. Ethical approval was obtained (08.12.2023), and written informed consent was secured from all participants. Results: Sixteen doctors were interviewed between December 2023 and February 2024. Analysis revealed two major themes: doctors’ knowledge, beliefs, behaviors, and organizational systems and processes. Awareness of AMDE reporting varied across participants, with some demonstrating familiarity with reporting mechanisms while others expressed uncertainty regarding definitions, reporting pathways, and perceived consequences. Beliefs regarding responsibility, fear of blame, time constraints, and lack of institutional support influenced reporting behaviors. Conclusion: The study demonstrates variability in doctors’ awareness and practices related to AMDE reporting, with several individual and systemic barriers contributing to underreporting. These findings highlight the need for targeted training, supportive institutional policies, and strengthened collaboration among clinicians, hospitals, industry, patients, and regulatory authorities to improve AMDE surveillance and patient safety.